The Taste for Bequests and Well-being of Widows: A Model of Life Insurance Demand by Married Couples - Fitzgerald, John M. (The Review of Economics and Statistics, 1989)
John M. Fitzgerald, The Taste for Bequests and Well-being of Widows: A Model of Life Insurance Demand by Married Couples, The Review of Economics and Statistics, Vol. 71, No. 2 (May, 1989), pp. 206-214